Strengthening Livestock Workforce Skills for Climate-Resilient Livestock Management: Policy Implications and Future Directions - Alifah, Nur (Livestock Science & Innovation Journal, 2024)
This study examines the role of workforce skill development in fostering climate resilience within the livestock sector, identifying gaps in training, policy support, and resource availability. Using a qualitative approach, data were collected through semi-structured interviews, questionnaires, and field observations. The research highlights key barriers to climate-resilient livestock management, including a lack of standardized training frameworks, inconsistent policy support, and limited access to adaptive resources. Findings indicate an urgent need for cohesive policy implementation and increased investment in climate adaptation resources. Farms with structured training programs showed a 30% improvement in adaptive livestock management, while workforces with access to climate-smart technologies reported a 25% increase in operational efficiency. Observational data revealed high adaptability among workers, emphasizing the potential of targeted training and technological integration in enhancing climate resilience. The impact is clear. A well-trained livestock workforce improves sustainability, mitigates climate risks, and strengthens food security. Policymakers should focus on standardizing training programs, aligning policies with climate adaptation goals, and allocating targeted funding to expand climate resilience efforts. Investment in digital training tools, climate forecasting technologies, and resource-sharing initiatives can further enhance workforce capabilities. This study contributes to the growing body of research on climate resilience by providing sector-specific recommendations for training standardization, policy alignment, and funding strategies. By prioritizing workforce development, the livestock sector can achieve long-term sustainability while addressing the economic and environmental challenges of climate change.